(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The last decade has seen a substantial increase in the number of international students in the USA, significantly influencing the fields of entrepreneurship and artificial intelligence (AI) innovation. This study examines how the influx of international talent has contributed to the growth and dynamism of the entrepreneurial ecosystem and AI sector. International students bring diverse perspectives, specialized skills, and innovative ideas that have fueled startup culture and technological advancements. They often bridge the gap between academic research and industry application, driving economic growth and competitiveness. This article explores the multifaceted impact of international students on entrepreneurship and AI innovation, highlighting key trends, contributions, and challenges faced over the past ten years.